ANALISIS DETERMINAN DEFISIT ANGGARAN DAN UTANG LUAR NEGERI DI INDONESIA - Satrianto, Alpon (Program Studi Magister Ilmu Ekonomi, 2015)
This study aims to determine (1) the effect of foreign debt, economic growth, exchange rates, oil prices, inflation and interest rates to the budget deficit in Indonesia. (2) the effect of the budget deficit, net exports, foreign exchange reserves, FDI, and savings investment gap on foreign debt in Indonesia. While this type of data is data documentary, the data source is a secondary data as well as data in the form of time series of the first quarter of 2000 - the fourth quarter of 2014. This study uses a simultaneous equation model analysis tool with Indirect Two Stage Squared method (TSLS). Endogenous variables in the study is the budget deficit and foreign debt. Whereas exogenous variables are economic growth, exchange rates, oil prices, inflation, interest rates, net exports, FDI, investment and savings gap and foreign interest rates. The study concluded that (1) foreign debt, economic growth, exchange rates, oil prices, inflation, and interest rates have a significant effect on the budget deficit in Indonesia. (2) budget deficit, net exports, foreign exchange reserves, FDI, and savings investment gap significantly influence the foreign debt in Indonesia. In other words, when the budget deficit rose, net exports declined, foreign exchange reserves decreased, FDI down, as well as foreign interest rates also decreased the budget deficit will increase. However, variables and savings investment gap does not significantly influence foreign debt in Indonesia. Based on these results the policies that can be recommended increase economic growth as measures to reduce the budget deficit, stabilize the prices of basic necessities that inflation is under control, keeping the exchange rate certainty so that exporters are not at a loss as well as the interest rate that can keep the investment climate. The conditions are expected to emerge from the economic certainty that may increase the state budget so avoid the problem of budget deficit. In addition, a reduction in the dependence on foreign debt can be achieved with fiscal discipline, maintain the balance of payments deficit, the reduction of foreign debt abroad and trying to divert the foreign debt into the country.Â Keywords : Budget Deficit, Foreign Debt Â